Teaching and Learning Electronic Music Composition - Heintz, Joachim (Revista Vórtex, 2020)
In this essay, composer Joachim Heintz presents his ideas and pedagogical strategies on teaching electronic music composition, specially within the current model found in universities around the globe. One of the important aspects investigated by Heintz is the complexity between teaching music composition and programming / instrument design, as well as the roles of professor and student (and what it means today). Through an organic and didactical methodology, Heintz describes his thoughts on teaching electronic music according to the German reality in universities and Hochschule: collective weekly seminar meetings and individual one-hour lessons. [note by editor].